Safety in steep slope logging operations. Issue 2 (3rd April 2019) - Garland, John; Belart, Francisca; Crawford, Robert; Chung, Woodam; Cushing, Tamara; Fitzgerald, Stephen; Green, Preston; Kincl, Laurel; Leshchinsky, Ben; Morrissette, Brett; Sessions, John; Wimer, Jeff
ABSTRACT: Partial results of a NIOSH-funded study for "Protecting the Logging Workforce: Development of Innovative Logging Techniques for a Safer Work Environment" by a team of researchers at Oregon State University are presented that review safety in steep slope logging. Comparisons are made for hazards and exposures of "conventional" and new technologies for steep slopes. Hazards of new technologies are identified. Safety assessments are addressed for forestry sectors internationally, for the firm and for workers. Important questions of technical feasibility, economic viability and environmental performance are raised. Ongoing research on operators using tethered and untethered systems are described. Results will help inform training and selecting operators. New Best Operating Practices and safety code regulations will result from the research. New technologies will reduce worker hazards and exposures for steep slope logging.